The taxation of capitalistic bequests - Kley, Verena (Gabler Verlag, 2012)
The taxation of bequests has long been and still is subject to intensive discussions in many industrialized countries. Triggered by these discussions, Verena Kley analyzes the taxation of bequests from economic perspectives, focusing on wealth transfers of very rich individuals. Given empirical findings, bequests of these individuals generate almost the entire revenues from wealth transfer taxation. Due to this, their specific preferences prove to be decisive for the optimal taxation of bequests. The author analyzes normative as well as positive implications for optimal wealth transfer taxation, accounting for a ,capitalist spirit' - traditionally associated with the upper tail of the wealth distribution.